Organ Donation Following Neurologic and Circulatory Determination of Death. (August 2018) - Nakagawa, Thomas A.; Shemie, Sam D.; Dryden-Palmer, Karen; Parshuram, Christopher S.; Brierley, Joe
Abstract : Objectives: To describe important considerations during the process of caring for critically ill children who may be potential organ donors and supporting the family during the death of their child. Design: Literature review and expert commentary. Measurement and Main Results: Medical literature focusing on pediatric donation, best pediatric donation practices, donor management, and factors influencing donation were reviewed. Additional pediatric data were obtained and reviewed from the U.S. Organ Procurement and Transplantation Network. Achieving successful organ donation requires the coordinated efforts of the critical care team, organ donation organization, and transplant team to effectively manage a potential donor and recover suitable organs for transplantation. Collaboration between these teams is essential to ensure that all potential organs are recovered in optimal condition, to reduce death and morbidity in children on transplantation waiting lists as well as fulfilling the family's wishes for their dying child to become a donor. Conclusions: Organ donation is an important component of end-of-life care and can help the healing process for families and medical staff following the death of a child. The process of pediatric organ donation requires healthcare providers to actively work to preserve the option of donation before the death of the child and ensure donation occurs after consent/authorization has been obtained from the family. Medical management of the pediatric organ donor requires the expertise of a multidisciplinary medical team skilled in the unique needs of caring for children after neurologic determination of death and those who become donors following circulatory death after withdrawal of life-sustaining medical therapies.